Gender, Voice and Online Space: Expressions of Feminism on Social Media in Spain - Willem, Cilia; Tortajada, Iolanda (Media and communication (Lisboa), 2021)
Feminism’s current momentum, encouraged by movements such as #NiUnaMenos or #MeToo, has caused many social media agents to adopt some degree of feminism as a part of their online image or personal brand. ‘Being a feminist,’ for some, has become a marketing strategy in times of great polarisation between progressive forces and a reactionary backlash against feminism. The appropriation of feminism by the global market challenges public opinion, media, and academia to think and rethink feminism, and to consider whether these changes have voided it of political meaning (Banet-Weiser, 2012, 2018; Gill, 2016b). In Spain, the (extreme) right is continually launching attacks against feminism. At the same time, minority collectives such as LGBTQ+ or Roma are helping to spread feminist values into the mainstream, denouncing one of its main struggles: structural and intersectional violence against women, including online hate and harassment. In this context of confrontation, social media agents are keeping the debate about feminism alive and are picking up Spanish grassroots movements’ claims (Araüna, Tortajada, & Willem, in press). In this article we outline the latest trends in feminist media research in Spain, examining 20+ years of postfeminism as an analytical tool, and highlighting new trends. Through recent research results, we show that in the Spanish (social) media landscape many different strands of feminism are entangled, all struggling to impose their narrative of what feminism looks like in the post-#MeToo era. We will examine the main fault lines along which feminism is divided into different undercurrents, some of which are fostering the progress of feminism, and some of which are undermining it: age (generation), class, race, and sexual identity.